Validation of a subjective global assessment questionnaire - Maiara P. Carniel; Daniele Santetti; Juliana S. Andrade; Bianca P. Favero; Tábata Moschen; Paola A. Campos; Helena A.S. Goldani; Cristina T.L. Dornelles (Brazilian Society of Pediatrics, 2015)
Objective: To validate the Subjective Global Nutritional Assessment (SGNA) questionnaire for Brazilian children and adolescents. Methods: A cross‐sectional study with 242 patients, aged 30 days to 13 years, treated in pediatric units of a tertiary hospital with acute illness and minimum hospitalization of 24 hours. After permission from the authors of the original study, the following criteria were observed to obtain the validation of SGNA instruments: translation and backtranslation, concurrent validity, predictive validity, and inter‐observer reliability. The variables studied were age, sex, weight and length at birth, prematurity, and anthropometry (weight, height, body mass index, upper arm circumference, triceps skinfold, and subscapular skinfold). The primary outcome was considered as the need for admission/readmission within 30 days after hospital discharge. Statistical tests used included ANOVA, Kruskal‐Wallis, Mann‐Whitney, chi‐squared, and Kappa coefficient. Results: According to SGNA score, 80% of patients were considered as well nourished, 14.5% moderately malnourished, and 5.4% severely malnourished. Concurrent validity showed a weak correlation between the SGNA and anthropometric measurements (p < 0.001). Regarding predictive power, the main outcome associated with SGNA was length of admission/readmission. Secondary outcomes associated included the following: length of stay at the unit after SGNA, weight and length at birth, and prematurity (p < 0.05). The interobserver reliability showed good agreement among examiners (Kappa = 0.74). Conclusion: This study validated the SGNA in this group of hospitalized pediatric patients, ensuring its use in the clinical setting and for research purposes in the Brazilian population.